Utilização dos sistemas integrados de gestão - ERP: estudo de múltiplos casos em pequenas e médias empresas - Maganha, Murilo Roberto Jesus [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Companies need strategies to improve their organizational performance, hence its financial returns and tools such as integrated management systems - ERP can help to maximize these returns. The ERP - Enterprise Resource Planning systems are enabling to integrate various functional and operational areas of the company, with the main feature as simultaneously managing multiple departments, improving their business processes. While feeding the decision-making process with information, support the company's business processes, integrating them and improving communication. This study aims to analyze the contributions of integrated systems - ERP in attending the company's needs in their business, as a very important tool for management and decision-making in the organizational context. The research is a multiple case study, whose sample was taken from customers of one of the largest suppliers of these systems in Brazil, chosen by convenience criteria (ease of access to campanies and their data) being composed by three small and medium-sized organizations of the State of São Paulo. Data were collected by questionnaires (open and closed) and interviews with people in the IT department of the surveyed companies, occupying functions in management and strategic levels. It was used as references for the development of the questionnaire, the variables base of the original model proposed by Mahmood and Soon (1991) and his adjustment made by Saccol et al. (2010) and the author of contributions resulting in a questionnaire composed of eight macro variables: Utility, Customers, Competitiveness of the company, Suppliers, market, Production: cost structure and capacity Efficiency and Effectiveness of the Organization and Interorganizational Efficiency. The results showed that the ERP systems, has a major role in the business context of SMEs, specially in variables Utility, Production: Cost structure/capacity and efficiency / effectiveness...

As empresas necessitam de estratégias que melhorem seus desempenhos organizacionais, consequentemente seus retornos financeiros e as ferramentas como os sistemas de gestão integrados - ERPs podem auxiliar a maximizar esses retornos. Os ERPs - Enterprise Resource Planning são sistemas de possibilitam integrar diversas áreas funcionais e operacionais da empresa, tendo como característica principal de atendimento simultâneo de vários departamentos, melhorando seus processos de negócio. Ao mesmo tempo em que alimentam o processo tomada de decisões com informações, oferecem suporte aos processos de negócios da empresa, integrando-os e melhorando a comunicação. Este estudo tem por objetivo analisar as contribuições dos sistemas integrados - ERP no atendimento das necessidades da empresa em seus negócios, como uma ferramenta de grande importância para o processo gerencial e decisório no contexto organizacional. A pesquisa é um estudo de múltiplos casos, cuja amostra foi retirada dos clientes de um dos maiores fornecedores desses sistemas do Brasil, escolhida por critérios de conveniência (facilidade de acesso às empresas e seus dados) sendo composta de três organizações de pequeno e médio porte do Estado de São Paulo. Os dados foram coletados com questionários (abertos e fechados) e entrevistas com pessoas da área de TI das empresas pesquisadas, ocupando funções em níveis gerenciais e estragégico. Foram utilizadas como referências para o desenvolvimento do questionário, as variáveis base do modelo original proposto pro Mahmood e Soon (1991) e as adaptação dele feita, por Saccol et al. (2010) e contribuições do autor, resultando em um questionário composto de oito macro variáveis estratégicas: Utilidade, Clientes, Competitividade da empresa, Fornecedores, Mercado, Produção: estrutura de custo e capacidade, Eficiência e Eficácia da Organização e Eficiência Interorganizacional...
Keywords: Sistemas integrados de gestão empresarial; Pequenas e médias empresas; Estudo de casos; Enterprise resource planning